(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the readiness to apply artificial intelligence (AI) in learning among medical students at Dai Nam University in 2025. Subjects and methods: A cross-sectional descriptive study was conducted among 568 medical students at Dai Nam University, using the MAIR-MS scale to measure students’ readiness to apply artificial intelligence. Data were collected through an online survey using a self-administered questionnaire. Results: The study was conducted on 568 medical students. The mean score for readiness to apply AI was 76.78/110, equivalent to 69.9% of the maximum total score. The vision and ethics factors had higher scores compared with the ability and cognition factors. The ability factor had a mean score of 27.97 ± 7.3/40, equivalent to 69,9% of the maximum score, followed by the cognition factor at 27.89± 7.5/40, equivalent to 69.7% of the maximum score, the ethics factor at 10.53 ± 2.81/15, equivalent to 70.2% of the maximum score, and the vision factor at 10.47 ± 2.81/15, equivalent to 69.8% of the maximum score. Conclusion: Medical students at Dai Nam University demonstrated a moderate-to-high level of readiness to adopt artificial intelligence (AI), although their foundational knowledge and competencies were lower than their vision and ethical awareness. The high proportion of neutral responses suggests that AI education has not yet been implemented in a sufficiently systematic manner. The university should develop a comprehensive AI curriculum with a clearly defined competency framework and assessment criteria, covering fundamental AI knowledge, practical AI application skills, the ability to critically evaluate the reliability of AI-generated outputs, and the associated legal and ethical considerations. In addition, future intervention studies or longitudinal research are needed to evaluate the real-world effectiveness of these educational programs.